Analisis Proses Pembelajaran Bahasa Arab Siswa Kelas VIII Madrasah Tsanawiyah Nurul Hidayah Way Kanan - Ita Nurmala; Masfiyatul Asriyah; M. Ari wibowo (Program Studi Pendidikan Bahasa Arab, 2022)
The purpose of this research is to analyze the process of learning Arabic at MTs Nurul Hidayah, looking for problems that impede learning, and knowing the solutions made by the teacher to overcome the problems that arise in the learning process. The questions in this study include